Molecular methods for cost-efficient monitoring of HAB (harmful algal bloom) dinoflagellate resting cysts. (October 2019) - Perini, F.; Bastianini, M.; Capellacci, S.; Pugliese, L.; DiPoi, E.; Cabrini, M.; Buratti, S.; Marini, M.; Penna, A.
Abstract: Cyst abundance and identity are essential for understanding and predicting blooms, and for assessing the dispersal of toxic target dinoflagellate species by natural or human mediated ways, as with ballast waters. The aim of this study was to apply rapid, specific and sensitive qPCR assays to enumerate toxic dinoflagellate cysts in sediment samples collected from Adriatic harbours. The molecular standard curves of various target species allowed obtaining the rDNA copy number per cyst. The analytical sensitivity for specific standard curves was determined to be 2 or 10 rDNA copies per reaction. The abundance varied in the range of 1–747 dinoflagellate cysts g −1 dry weight. The assays showed greater sensitivity as compared to counts by light microscopy. This qPCR method revealed a powerful tool for the quantification of cysts from toxic dinoflagellate resting stages in sediment samples from Adriatic ports. Graphical abstract: Unlabelled Image Highlights: Cysts of toxic dinoflagellate species can be dispersed by ballast waters in the Adriatic ports. We applied qPCR assays to monitor and quantify cysts from toxic species in sediment from ports. The quantification was done by species-specific standard curves. The qPCR assays can be applied in monitoring activities to assess environmental port quality.